4D printing of shape memory polymer composites: A review on fabrication techniques, applications, and future perspectives. (September 2022) - Khalid, Muhammad Yasir; Arif, Zia Ullah; Noroozi, Reza; Zolfagharian, Ali; Bodaghi, Mahdi
Abstract: In recent years, there has been rising interest in additively manufactured shape memory polymers (SMPs) and their multi-functional composites. Four-dimensional (4D) printing is an intriguing additive manufacturing field, which uses time-responsive programmable materials. Stimuli-responsive polymers present an ability to retain their original shapes from a programmed temporary shape upon exposure to different external stimuli including heat, light, electricity, humidity, or magnetism. In recent years, rapid technological developments have been made in the field of smart and multi-functional materials by integrating 4D printing (4DP) and shape memory polymer composites (SMPCs). 4DP of SMPCs helps in exploring the myriad engineering applications including automotive, soft robotics, food, smart textiles, biomedical devices, mechatronics, and wearable electronics. Herein, this review article presents important 4DP technologies in conjunction with the underlying functionalities of stimuli-responsive polymer composites. This review also elucidates the future opportunities of 4D-printed SMPCs in terms of preprogramming knowledge, multi-way SMPCs, multi-material printing, sustainability, and potential applications. Finally, based on the characteristics of the SMPCs employed for each technology illustrative examples of the principal applications are provided. It is anticipated that the insightful exploration of this novel field could support future advancements as well as spur innovations in the 4DP field. Graphical abstract: Unlabelled Image